2019
DOI: 10.29333/ejgm/94091
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of gratitude on psychological well-being and quality of life among hospitalized substance abuse patients

Abstract: Background: Substance abuse is a chronic phenomenon that affects many physical, psychological, social, familial and economic elements. Objective: This study was conducted in order to investigate the effectiveness of gratitude on individual's well-being as well as the quality of life (QoL) of hospitalized substance abuse patients. Methods: The current study was clinical trial study. The research was conducted on 64 addicted patient which had been referred to the addiction rehabilitation center (Modarres hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…In addition, 78% felt that they needed for education to announce the bad news for the patients and this education is recommended to provide at the beginning of their education (25). Psychological and behavioral training in the provision of health services, and the evaluation of its results, have been emphasized in various studies (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 78% felt that they needed for education to announce the bad news for the patients and this education is recommended to provide at the beginning of their education (25). Psychological and behavioral training in the provision of health services, and the evaluation of its results, have been emphasized in various studies (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Expressing gratitude can improve well-being, including physical and mental health. 6,18,19 Practicing gratitude in one's personal and professional life is a powerful tool to improve overall quality of life. Nurses work in a complex, highly stressful environment and strategies are employed to reduce burnout and promote well-being, with gratitude as one strategy.…”
Section: Nursing Gratitude Practicementioning
confidence: 99%
“…Studies found PFs expressing gratitude to providers had a positive impact on patients' healing, care experience, 32,33 psychological well-being, quality of life, 19 physical well-being, stress reduction, anxiety reduction in the face of death 6 and customer loyalty to a provider or organization. 2,34 Moreover, expressing gratitude can help with the grieving process for families.…”
Section: Patient and Family Gratitude And Nursing Carementioning
confidence: 99%
See 1 more Smart Citation
“…( ‫اسة‬ ‫در‬ ‫في‬ ‫كما‬ ‫الجامعة؛‬ ‫طمبة‬ ‫لدل‬ ‫النفسي‬ ‫الضغط‬ ‫مستكل‬ Mccullough et al, 2002;Hong Yi, 2006;Froh et al, 2009;Satici et al, 2014;Deasy et Cunha et al, 2019;Finucane,2010;Geier & Morris, 2022;Ghalesefidi et al, 2019;Killen & Macaskil, 2015;Nathan et al, 2019;Noor et al, 2018;Sadeghi& Pour, 2015;Sahar et al, 2021;AL-Seheel, 2018;Xiaotong, 2017 .) Ghalesefidi et al, 2019;Killen & Macaskil, 2015;Nathan et al, 2019;Noor et al, 2018;Sadeghi & Pour, 2015;Sahar et al,…”
unclassified